Influence of Different Seating and Crank Positions on Muscular Activity in Elite Handcycling - A Case Study. (2015) - Litzenberger, Stefan; Mally, Franziska; Sabo, Anton
Abstract: Due to rising public focus scientiﬁc analysis of performance parameters is getting more and more important in paralympic sports. Several studies have been performed to investigate different design parameters of handcycles (e.g. crank length) already; however, most of those were done with able-bodied subjects, widely unfamiliar to handcycling. In this study bilateral surface electromyography (sEMG) of several muscles of the upper body and arms of an elite handcyclist (multiple medal-winner in Paralympic Games and World Championships) is performed with different crank lengths, crank positions and backrest positions at power levels of 130, 160 and 190 W resulting in a total of 22 measurements. sEMG data were recorded bilaterally at a recording frequency of 1000 Hz using Ag/AgCl electrodes. Concurrently the crank position was acquired with ten Vicon Bonita infrared cameras recording at 100 Hz. EMG data were rectiﬁed, smoothed and normalized to crank-cycle duration (0-360 deg) for each single crank-cycle. Phases of activity for each muscle (i.e. EMG amplitude exceeds 30% of maximum amplitude) and integrated EMG (iEMG) as an indicator for net muscular e ort were calculated. Results showed that amplitude and iEMG were higher for higher power output and shorter cranks, crank and backrest position inﬂuenced several muscles but results were always similar for similar shoulder-crank-distances. It could be shown, that muscular effort is clearly inﬂuenced by the handcycle parameters investigated and that these measurements can be used to individually optimize the position in a handcycle with regard to muscular effort.